2020
DOI: 10.2147/ott.s238832
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Evaluating the Therapeutic Potential of Zanubrutinib in the Treatment of Relapsed/Refractory Mantle Cell Lymphoma: Evidence to Date</p>

Abstract: Mantle cell lymphoma (MCL) is an uncommon B-cell non-Hodgkin lymphoma characterized by an aggressive clinical course in the majority of patients. Despite recent improvements in outcomes, MCL remains incurable and a major therapeutic challenge. BTK inhibitors are the preferred treatment option for patients with relapsed/refractory MCL, including those unfit for chemotherapy or those with chemoresistant disease. In addition to ibrutinib and acalabrutinib, the FDA recently approved zanubrutinib for the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…A safety analysis from 6 zanubrutinib monotherapy trials showed that grade ≥ 3 bleeding occurred in 2.1% of 682 patients ( 5 ). Compared with ibrutinib, the rate of major bleeding with zanubrutinib is lower ( 13 ), which is supported by a phase III study (ASPEN study) ( 4 ).…”
Section: Discussionmentioning
confidence: 79%
“…A safety analysis from 6 zanubrutinib monotherapy trials showed that grade ≥ 3 bleeding occurred in 2.1% of 682 patients ( 5 ). Compared with ibrutinib, the rate of major bleeding with zanubrutinib is lower ( 13 ), which is supported by a phase III study (ASPEN study) ( 4 ).…”
Section: Discussionmentioning
confidence: 79%
“…A Zanubrutinib (ZBB/BGB-3111) is classified as a (BTK) Bruton tyrosine kinase inhibitor [1][2][3] through possible antineoplastic drug and it is given through mouth in the form of tablet dosage. This drug was approved by FDA in September 2019 [4], newly approved by the USA and Chinese drug supervisory establishments for the treatment of (MCL) mantle cell lymphoma [5], liver injury patients [6], and the commercial brand name is Brukinsa, ZBB is used for the action of grown people (adults) with mantle cell lymphoma (MCL) [7][8][9][10], who have consumed at minimum one prior treatment [11]. The molecular weight of zanubrutinib (C27H29N5O3) is 471.56.…”
Section: Introductionmentioning
confidence: 99%
“…Efficiency was assessed in (NCT 02343120) BGB-3111-AU-003, a phase I/II growth, open-label, multi-centre, the single-arm, global trial of B cell malignancies [13,14], with 32 earlier treated Mantle-cell lymphoma (MCL) patients treated with ZBB managed per day two times with 160 mg [15][16][17] of ZBB or per day one time 320 mg of ZBB in the form of tablet dosage [18]. Zanubrutinib provides a higher response rate (84%) and prolonged progression-free survival (PFS) in patients with refractory or relapsed Mantle-cell lymphoma (MCL) [19]. These mixtures have established deep replies with several patients achieving undetectable minimal residual disease (uMRD) [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Zanubrutinib is a treatment medication marketed to adults under the trade name Brukinsa who have already undergone treatment with the Mantle Cell Lymphoma (MCL). 1,2 Efficacy has been evaluated in 86 patients with mantle cell lymphoma (MCLs) who received at least one previous therapy 3 under Phase II, open-label, multicenter, single-arm test BGB-3111-206 (NCT03206970). In phase I/II, open-label, dose escalation, global, multicenter, onearm test of B cell malignancies was also evaluated for efficacy in BGB-3111-AU-003 (CNT02343120).…”
Section: Introductionmentioning
confidence: 99%